New approaches to the prognosis of pre-eclampsia in pregnant woman - T. O. Loskutova (Zaporozhye State Medical University, 2018)
Objective: development and evaluation of the effectiveness of the method for predicting pre-eclamapsia in pregnant women by testing thrombophilia genes, measuring the levels of antibodies to β2 glycoprotein-1, D-dimer and coefficient of atherogenicity. Materials and methods: This retrospective, case-control study was conducted on 156 patients who were in third trimester of pregnancy: 112 with PE and 44 healthy normotensive pregnant women. A combined approach to the prognosis of preeclampsia which is based on the level of D-dimer (immunоturbodimetric analysis), the value of the atherogenicity coefficient, the number of antibodies to β2 glycoprotein-1 (ELISA-analysis), the presence of polymorphism 455 G → A in the gene of fibrinogen β and 675 4G/5G in the gene of the plasminogen activator inhibitor type 1 (PCR) was proposed. Results: It was established that the sensitivity of the proposed prognostic model was 82.5 % (95 % CI 74.2-88.9 %), specificity 90.9 % (95 % CI 78.3-97.5 %). The model takes into account the role in pre-eclampsia development not only of each individual factor, but also of their combination. Approbation of the prognostic model in the group of pregnant women in the first trimester of pregnancy showed its high efficacy: the incidence of PE in the group with a predicted low risk of developing PE was 2.5 % versus 57.1 % in the group with a predictable high risk (p<0.05). Conclusions. The proposed model has good prognostic features, which allow assessing the risk of pre-eclampsia development in pregnant women with high probability beginning from first trimester of pregnancy. Objective: development and evaluation of the effectiveness of the method for predicting pre-eclamapsia in pregnant women by testing thrombophilia genes, measuring the levels of antibodies to β2 glycoprotein-1, D-dimer and coefficient of atherogenicity. Materials and methods: This retrospective, case-control study was conducted on 156 patients who were in third trimester of pregnancy: 112 with PE and 44 healthy normotensive pregnant women. A combined approach to the prognosis of preeclampsia which is based on the level of D-dimer (immunоturbodimetric analysis), the value of the atherogenicity coefficient, the number of antibodies to β2 glycoprotein-1 (ELISA-analysis), the presence of polymorphism 455 G → A in the gene of fibrinogen β and 675 4G/5G in the gene of the plasminogen activator inhibitor type 1 (PCR) was proposed. Results: It was established that the sensitivity of the proposed prognostic model was 82.5 % (95 % CI 74.2-88.9 %), specificity 90.9 % (95 % CI 78.3-97.5 %). The model takes into account the role in pre-eclampsia development not only of each individual factor, but also of their combination. Approbation of the prognostic model in the group of pregnant women in the first trimester of pregnancy showed its high efficacy: the incidence of PE in the group with a predicted low risk of developing PE was 2.5 % versus 57.1 % in the group with a predictable high risk (p<0.05). Conclusions. The proposed model has good prognostic features, which allow assessing the risk of pre-eclampsia development in pregnant women with high probability beginning from first trimester of pregnancy.